(3GdQSGdI GdMGJejI (B((3ef MceI CQSWGWGdjS hTYQ CHj GdWjH GdeJfHi(B)s - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s ((3eMeO Hf GHQGgje Hf eci Hf eMSf GdbjQhGfi s)
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efgG (B: (3bGd CQSWGWGdjS GPG cGfJ GdCTjGA aGYdg HGdWHY de JMeO Ydi aYdgG s
(3BNQgG (B:s
(3hZGjI GdeaQW ai Sdeg cZGjI GdeaQW ai MQHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI eYGQVIs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B82 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B56s
Keywords: (3GdCOHs